Joshua Ratoon Sands correspondence - Sands, Joshua Ratoon, 1795-1883.
ALS written by Sands aboard the U.S.S. Falmouth at Havana, Cuba, to Thomas W. Rodney, American consul in Cuba.
Naval officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Rodney, Thomas W. -- Correspondence; Falmouth (Ship); Diplomatic and consular service, American -- Cuba; Havana (Cuba) -- History, Naval -- 19th century; Naval officers